2009
DOI: 10.2308/jiar.2009.8.2.1
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Adoption of IFRS, Managerial Incentives, and Value-Relevance: Some French Evidence

Abstract: This paper investigates whether and how managerial incentives influence the decision to elect optional exemptions when first adopting International Financial Reporting Standards (IFRS). It also examines the value-relevance of the mandatory and optional equity adjustments that must be recognized as a result of the first-time adoption of IFRS. Both questions are addressed in the context of the mandatory adoption of IFRS by French firms in 2005. Three major findings emerge from our analyses. First, managerial inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 19 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Also they provide that in the last years the earnings played an increasingly declining mission in the stock prices relative to book values of the latest sample. Referring to the research of O'Hanlon and Pope (1999); Cormier et al (2009), Agostino et al (2010); Inchausti and Pérez (2011); Devalle and Magarini (2012), Vo (2017), Robinson et al (2017), the book value has a positive effect on the stock price valuation. From the above discussion it can be derived a hypothesis: H2: Firm's book value per-share positively affect stock price.…”
Section: Literature Review and Hypothesismentioning
confidence: 95%
See 1 more Smart Citation
“…Also they provide that in the last years the earnings played an increasingly declining mission in the stock prices relative to book values of the latest sample. Referring to the research of O'Hanlon and Pope (1999); Cormier et al (2009), Agostino et al (2010); Inchausti and Pérez (2011); Devalle and Magarini (2012), Vo (2017), Robinson et al (2017), the book value has a positive effect on the stock price valuation. From the above discussion it can be derived a hypothesis: H2: Firm's book value per-share positively affect stock price.…”
Section: Literature Review and Hypothesismentioning
confidence: 95%
“…The other several studies conduct in different European contexts such those of Wang et al (2006);Inchaustirt al. (2007); Oswald (2008); Cormier et al (2009); Devalle and Magarini (2012) show that earnings per-share affect to the stock prices.…”
Section: Literature Review and Hypothesismentioning
confidence: 95%
“…Comparable conclusions are made by Bartov et al (2005), who identify that the value relevance of IFRS earnings of German voluntary adopters is higher than the value relevance under German GAAP. Cormier et al (2009) focus on French mandatory IFRS adopters and detect the value relevance of mandatory equity adjustments made on the transition from local GAAP, which can be perceived as a positive signal of IFRS adoption to enhance value relevance. Using a sample of mandatory adopters from 12 EU countries, Aubert and Grudnitski (2011) do not detect any incremental increase in the value relevance of accounting information after IFRS adoption.…”
Section: Ifrs Adoption and Value Relevance Of Particular Accounting V...mentioning
confidence: 99%
“…Nevertheless, the empirical evidence does not always confirm the expectations and real economic outcomes remain inconclusive, e.g. Bartov et al (2005), Barth et al (2008), Cormier et al (2009), Morais and Curto (2009), Aubert and Grudnitski (2011).…”
Section: Introductionmentioning
confidence: 95%
“…However, the process of adoption has been the subject of limited research, since researchers themselves have suggested that it would be better to use national case studies to analyze the adoption of IFRS in individual nations. Examples of this are Callao-Jarne-Lainez (2007) in Spain, Cormier-Demaria-Lapointe-Teller (2009) in France, Lantto and Sahlström (2009) in Finland, Iatridis and Rouvolis (2010) in Greece, Peng and Smith (2010) in China and Beke (2010b) in Hungary also.…”
Section: Previous Related International Literature Reviewmentioning
confidence: 99%